这道题应该是写错了吧,倒推得c=-1,a+b=1,ab=0于ab=(c+2)^2 矛盾!
a+b=c+2=ab-c如何推出ab=2c+2(a+b)^2=(c+2)^2
1个回答
相关问题
-
己知A=4a2b+2ab2+c,B=a2b+ab2+b,C=5/2ab+3/2ab2-1/2a.求:A+B-2C.
-
(1) a+b>c+d,(2) b+d>a+c 如何通过(1),(2)推出 b>c
-
(c-2ab+a+b)(a-2+b+c)+(1-ab)^2因式分解
-
a2(b+c)2+b2(c+a)2+c2(a+b)2+abc(a+b+c)+(a2+b2+c2)(ab+bc+ca)因式
-
A=(b^2+c^2-a^2)/2bc,B=(a^2+c^2-b^2)/2ac,C=(a^2+b^2-c^2)/2ab
-
为什么(a+b+c)^2-3(a^2+b^2+c^2) =0 能推出(a-b)^2+(a-c)^2+(b-c)^2=0
-
a^3+b^3+c^3-3ab=(a+b+c)(a^2+b^2+c^2-ab-ac-bc)=1/2(a+b+c)[(a-
-
(a+b+c)(a^2+b^2+c^2-ab-ac-bc)+3ab=
-
(c-2ab+3a)(2b+c-3a)与(a-b)(a+b)^2-2ab(a^2-b^2)
-
a^2+b^2+c^2-ab-bc-ac=1/2[(a-b)^2+(b-c)^2+(c-a)^2]